2021
DOI: 10.3389/fgene.2020.618614
|View full text |Cite
|
Sign up to set email alerts
|

Male-Dominated Migration and Massive Assimilation of Indigenous East Asians in the Formation of Muslim Hui People in Southwest China

Abstract: The origin and diversification of Muslim Hui people in China via demic or simple cultural diffusion is a long-going debate. We here generated genome-wide data at nearly 700,000 single nucleotide polymorphisms (SNPs) from 45 Hui and 14 Han Chinese individuals collected from Guizhou province in southwest China. We applied principal component analysis (PCA), ADMIXTURE, f-statistics, qpWave, and qpAdm analysis to infer the population genetic structure and admixture history. Our results revealed the Guizhou Hui peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 32 publications
5
27
0
Order By: Relevance
“…For example, statistically negative f 4 (Western Eurasians, Eastern Eurasians; SYH, Mbuti) quantitatively illuminated SYH people shared more alleles with East Asians and Southeast Asians compared with Western Eurasians, which was consistent with the higher estimated Eastern Eurasian-related ancestry proportion in the qpAdm and qpGraph models. Recent genetic studies based on the central Guizhou and Sichuan Huis, northwestern Ningxia, and Xinjiang Huis also showed eastern Eurasian affinity of their studied Hui people (Liu et al, 2021b;Ma et al, 2021;Wang et al, 2020a). Taken together, we concluded that geographically different Chinese Hui people derived their primary ancestry from East Asians although they remain unique Islam culture and dietary habits.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…For example, statistically negative f 4 (Western Eurasians, Eastern Eurasians; SYH, Mbuti) quantitatively illuminated SYH people shared more alleles with East Asians and Southeast Asians compared with Western Eurasians, which was consistent with the higher estimated Eastern Eurasian-related ancestry proportion in the qpAdm and qpGraph models. Recent genetic studies based on the central Guizhou and Sichuan Huis, northwestern Ningxia, and Xinjiang Huis also showed eastern Eurasian affinity of their studied Hui people (Liu et al, 2021b;Ma et al, 2021;Wang et al, 2020a). Taken together, we concluded that geographically different Chinese Hui people derived their primary ancestry from East Asians although they remain unique Islam culture and dietary habits.…”
Section: Discussionsupporting
confidence: 60%
“…We not only identified a significant genetic differentiation between SYH and central Chinese Hui people from Guizhou and Sichuan but also found the differentiated genetic admixture history between SYH people and indigenous Hainan Tai-Kadai populations and Vietnam Cham people. Our findings reported here suggested the more complex landscape of the demographic history of Chinese Hui people than previously reported two-source admixture models (Liu et al, 2021b;Ma et al, 2021;Wang et al, 2020a) and provided insights into the formation of southernmost Hui people, which was formed via a mixture of tripartite sources from EA, CV and CSA.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…We subsequently explored the genetic similarities and differences within and between Tanka people and their adjacent East Asians(Chen et al, 2021; He et al, 2021; Y. Liu et al, 2021; Lu et al, 2020; Jin Sun et al, 2020; Q. Wang et al, 2020; Yao et al, 2021) based on the genetic variants of denser SNP data (approximately 700K).…”
Section: Resultsmentioning
confidence: 99%